Importance of Social Media interactions at AASW6 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Worlali Senyo highlights the importance of Social Media interactions during the Africa Agriculture Science Week. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/